2022
DOI: 10.3390/pathogens11040421
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the Beta-Proteobacterial Genus Ca. Ichthyocystis: A Case Report of Epitheliocystis in the Pompano Trachinotus ovatus

Abstract: Epitheliocystis is a disease caused by a wide variety of host-specific intracellular bacteria infecting fish gills. In the Mediterranean Sea, epitheliocystis has been recently associated with a novel genus of beta-proteobacteria, the Ca. Ichthyocystis genus. In the present study, we report a case of epitheliocystis in a wild-caught specimen of pompano Trachinotus ovatus in Crete, Greece. Molecular analysis of partial 16s rRNA sequence led to the discovery of a putative novel species of the Ca. Ichthyocystis ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…4 ). This is in compliance with previous phylogenies using 16S rRNA sequences (Contador et al 2016 ; Seth-Smith et al 2016 ; Cascarano and Katharios 2022 ; Cascarano et al 2022 ). Consequently, it is reasonable to believe that all taxa of this clade share the same common ancestor of Cand .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…4 ). This is in compliance with previous phylogenies using 16S rRNA sequences (Contador et al 2016 ; Seth-Smith et al 2016 ; Cascarano and Katharios 2022 ; Cascarano et al 2022 ). Consequently, it is reasonable to believe that all taxa of this clade share the same common ancestor of Cand .…”
Section: Discussionsupporting
confidence: 91%
“…Ichtyocystis hellenicum). Recent studies have identified new agents of this genus associated with epitheliocystis in reared greater amberjack ( Seriola dumerili ), wild-caught Pacific herring ( Clupea pallasii ) and Pacific mackerel ( Scomber japonicus ) (Cascarano et al 2022 ), as well as from pompano ( Trachinotus ovatus ) (Cascarano and Katharios 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations